2011
DOI: 10.2190/om.62.2.d
|View full text |Cite
|
Sign up to set email alerts
|

Motivation for Research Participation among People Bereaved by Suicide

Abstract: Few studies directly address vulnerable populations' motivation for participating in research. Often motives are expressed spontaneously and typically given post-interview. This article investigates motivation for research participation among informants who have been bereaved by suicide. Informants were specifically asked for their motivation either prior to, or directly after the interview. Four categories of motivations were identified: (1) Helping Others, (2) Venting, (3) Insight, and (4) Just Because. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
6
24
0
Order By: Relevance
“…This shows the value of letting the respondents themselves rate if they were negatively affected or not since the respondents are the only ones that can put this question in a context of their whole situation. The wording ‘negative or positive’ might, however, be misleading since immediate undesirable reactions may be beneficial in the long term, a possibility that was also suggested by the participants themselves (Dyregrov, 2004 ; Jorm et al 2007 ; Dyregrov et al 2010 ). Some parents also referred to practical issues when they rated being ‘negatively affected’ and if they regretted their research participation, which shows that different evaluation criteria were used when answering the questions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This shows the value of letting the respondents themselves rate if they were negatively affected or not since the respondents are the only ones that can put this question in a context of their whole situation. The wording ‘negative or positive’ might, however, be misleading since immediate undesirable reactions may be beneficial in the long term, a possibility that was also suggested by the participants themselves (Dyregrov, 2004 ; Jorm et al 2007 ; Dyregrov et al 2010 ). Some parents also referred to practical issues when they rated being ‘negatively affected’ and if they regretted their research participation, which shows that different evaluation criteria were used when answering the questions.…”
Section: Discussionmentioning
confidence: 97%
“…In the introductory letter we therefore addressed the parents as ‘someone who has lost a son or daughter in a sudden death’ and someone ‘who has not lost a son or daughter’ and emphasized that the questionnaires were developed together with suicide-bereaved parents. We also forewarned participants that some of the questions could raise difficult emotions, although participants in similar studies often perceived the participation as valuable (Dyregrov, 2004 ; Jorm et al 2007 ; Dyregrov et al 2010 ). In the introductory letter we emphasized that participation was voluntary and informed about the possibility to end participation at any time without further explanation (Jorm et al 2007 ).…”
Section: Methodsmentioning
confidence: 99%
“…Literature reporting on the motivation for participating in suicide-related research suggests the dominance of altruism and a desire to help others. This is characterised by expressing hope that sharing their story will contribute to research that will help advance the field to better support others [22,26] or prevent suicide [27]. Altruism and a desire to ease others' future difficulties consistently emerges as a motivation for research on topics beyond suicide [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants have reported additional benefits of research participation, including gaining insights from working through grief elements previously unaddressed and sharing their story with others. The latter point can contribute to increased understanding, meaning-making, and meaning reconstruction after a loved one's death [22,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, suicide survivors were noted to state that the reasons for their involvement in research studies regarding suicide bereavement were to vent, gain insight into their own experiences, and have contact with a mental health professional. Essentially, they are seeking suitable forums for communications about their experiences (Dyregrov et al, 2010), which they have found difficult to access. Consequently, it is imperative that nurses and other health care professionals are well prepared and practice reflectively to acknowledge how their communication may be perceived by bereaved people (Botha et al, 2009;Maple et al, 2010).…”
Section: Discussionmentioning
confidence: 99%